Design and anlaysis of a tidal current turbine - Zhang, Bujie (2009)
The wind turbine power generator has been widely used in many countries for commercial electricity power station. And the present tidal power station has a lot of limitations such as location, steady power output requirement. In this project, the blade element and momentum (BEM) theory is used to design optimal blades for tidal turbines for the new generation of tidal power station without dam. After the models designed in Solidworks, the CFD (computational fluid dynamics) method is used to do the analysis and redesign for the models based on simulation results. The simulations are based on various blades chord sizes and twisted angles. The objectives are to find out the relationship between power generation and tip speed ratio. Furthermore various operating tip-speed ratios will be considered in this project to determine the optimal tip speed ratio for the highest power output.